Experimental Determination and Comparative Analysis of the PPH030GP, ABS and PLA Polymer Strength Characteristics at Different Strain Rates - M. Yu. Zalohin; V. V. Skliarov; Ja. S. Dovzhenko; D. A. Brega (Наука и техника)
Nowadays the field of application of products made from polymer materials is constantly increasing. These products find their wide application in the most high-tech industries such as automotive, aerospace and medical industry. Modern trends in the development of the automotive industry predicts that 75 % of the total car mass will be replaced with polymer materials by 2020 and other industries demonstrate similar trends. Regarding to this information, engineering companies that design parts of the automotive industry should have polymer material characteristics over an entire range of deformations up to destruction for their performance prediction. However, strength characteristics of products from polymers are different and depend not only on a polymer grade but also on technology used for part production. Existing literature review on this problematic area is rather rare. The purpose of this paper is to determine and analyze mechanical characteristics of widely used PPH030GP polymer obtained by extrusion and ABS, PLA polymers applied while manufacturing samples using an additive method (3D-printing) depending on the rate of high-elastic deformation. All the samples have been made according to the requirements of GOST 11262–80 and subjected to uniaxial stretching on a tensile machine UIT STM 050/300 at different speeds of clamp expansion. According to experimental results, stretching diagrams in conditional coordinates s–e have been obtained up to the point of failure for different rates of clamp expansion. It has been shown that while using the additive method, a direction of layers and adhesion between them, which depends on 3D-print parameters, have a significant effect on the part strength. Printing settings are indicated in accordance with the selected mode and a 3D-printer model. As a result of data processing, strength characteristics of PPH030GP polymer and ABS and PLA polymers have been determined to a sufficient extent, depending on the direction of printing layers and rate of high-elastic deformation. These data can be used to calculate strength of products by numerical methods and a finite element method in various software products.